Assessment of road infrastructure in the Bangsamoro areas in the context of inclusive mobility the case of Maguindanao Province - Abusama, Muslima K. (School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
Most of the communities in the Bangsamoro area have a transportation system that is unreliable, insufficient, and with poor road quality/conditions that results to high poverty. The main objectives of the study is to assess the existing road infrastructure facilities and understand the disparities between the most accessible and the less accessible areas, which in turn can enhance road infrastructure to attain inclusive mobility in the Bangsamoro areas focusing on the Province of Maguindanao. Descriptive research method was employed to answer the research problems and attain relevant findings that will address the objectives of this study. The researcher made use of household survey, key informant interview and field observation to gather all data needed in this study. Assessment of road infrastructure in the study area shows that municipal and barangay roads are of low conditions. Improvement of road pavements to access health, educational, employment and, places of worship services is needed to enhance mobility and reduce social inequalities. The Local Governments Units and its policy makers need to look at policy recommendations to ensure improvement of road maintenance and investments that will work and help reduce poverty in the study area.